The Effectiveness of Mobile Apps Based Interactive Multimedia to Improve Students' Conceptual Understanding of Human Digestive System Material (Journal of Biology Education, 2023)
Online learning causes students to have difficulty understanding concepts. Students need interesting and interactive learning media without space and time limitations such as interactive multimedia based on mobile apps. The purpose of this study was to analyze the effectiveness of the interactive multimedia of the human digestive system based on mobile apps to increase students' understanding of concepts and to analyze the profile comparison of their conceptual understanding. This type of research used nonequivalent control group design, XI MIPA 1 as the experimental class using interactive multimedia and XI MIPA 2 as the control class using video. Data analysis using test instruments and questionnaires. The results showed that there was a significant difference in the average learning outcomes in the experimental class compared to the control class with an average value of 81.8 > 76.1. The increased understanding of concepts in the experimental class and the control class were in the moderate category and significantly different with an N-gain 0.63 > 0.48. The class that completes classically is the experimental class with a score of 88.89%. The profile of understanding the concept of the experimental class is higher than the control class on all indicators. The experimental class gave a good to very good response and the teacher gave a very good response to the application of interactive multimedia. The conclusion of this study is that the interactive multimedia of the human digestive system based on mobile apps is effective for increasing students' understanding of concepts and the profile of students' conceptual understanding in the experimental class is higher than that of the control class.